Desenvolvimento e teste de um sistema para separação automática das fases glicerol-biodiesel utilizando sensor de condutividade elétrica - Santos, Paulo Sérgio Barbosa dos [UNESP] (2013)
In the production of biodiesel on a small scale decanters are commonly utilized to separate the glycerol from biodiesel produced after a chemical reaction of oil with some alcohol and a catalyst. In most cases, this separation process is done manually and subjectively by an operator that can make mistakes in interpretation, increasing the cost of production and/or compromising the quality of the fuel produced. This work presents a methodology for developing and testing of a micro controlled electronic system, capable of distinguishing the phases formed after the decanting process by means of an electrical conductivity sensor, which permits the actuation of valves in order to have an automatic control of the direction of biodiesel and glycerol for different reservoirs. This methodology contains the technical development including modeling, computer simulation, materials selection, manufacturing, electronic project, calibration and obtains the performance characteristics of the sensor. The system consists of an electrical panel, which allows to observe the process through features an LCD display and permits change the settings of microcontroller through the USB communication device with a computer. The system proved effective in tests with biodiesel and glycerol production processes with refined soybean oil, and glycerin showed conductivity value higher than biodiesel as expected